Map-based cloning of the APRR2 gene controlling green stigma in bitter gourd (Momordica charantia) - Zhan, Jinyi; Zhong, Jian; Cheng, Jiaowen; Wang, Yuhui; Hu, Kailin (Frontiers in Plant Science, 2023)
Bitter gourd is an economically important vegetable and medicinal crop marked by its bitter fruits. Its stigma color is widely used to assess the distinctiveness, uniformity, and stability of bitter gourd varieties. However, there has not been sufficient researches dedicated to genetic basis of its stigma color. In this study, through bulked segregant analysis (BSA) sequencing, we identified a single dominant locus McSTC1 at pseudochromosome 6 by utilizing genetic mapping using an F2 population (n =241) derived from the cross between green and yellow stigma parental lines. An F2-derived F3 segregation population (n = 847) was further adopted for fine mapping, which delimited the McSTC1 locus to a 13.87-kb region containing one predicted gene McAPRR2 (Mc06g1638), a homolog of the Arabidopsis two-component response regulator-like gene AtAPRR2. Sequence alignment analysis of McAPRR2 revealed that a 15-bp insertion at exon 9 results in a truncated GLK domain of its encoded protein, which existed in 19 bitter gourd varieties with yellow stigma. A genome-wide synteny search of the bitter gourd McAPRR2 genes in Cucurbitaceae family revealed its close relationship to cucumber CsAPRR2, melon CmAPRR2, and watermelon ClaAPRR2 that are corresponding to white or light green fruit skin. Our findings contribute to the molecular marker assistant breeding for bitter melon stigma color, as well as its underlying genetic basic.